2004
DOI: 10.1160/th04-06-0337
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin for the prophylaxis of thromboembolism in women with prosthetic mechanical heart valves during pregnancy

Abstract: Increased thromboembolic events occur in women with mechanical prosthetic valves during pregnancy, and selecting an effective and safe anticoagulant is still a challenge. Low molecular weight heparin (LMWH) is a promising alternative, but a recent warning and label change about its use in patients with mechanical prosthetic valves has caused confusion among physicians. The aim of the present study was to review the risks of maternal and fetal complications with mechanical heart valves treated with LMWH during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(36 citation statements)
references
References 35 publications
2
32
0
2
Order By: Relevance
“…49,50,[332][333][334][335][336][337][338][339][340] In a systematic review of observational studies between 1966 and 1997 that reported on outcomes with various anticoagulant regimens in pregnant women with mechanical prosthetic valves, the regimen associated with the lowest risk of valve thrombosis/systemic embolism was the use of vitamin K antagonists throughout pregnancy (3.9%). 49 The use of UFH in the fi rst trimester and near term was associated with a higher risk of valve thrombosis (9.2%).…”
Section: Anticoagulant Management Of Mechanical Prosthetic Valves In mentioning
confidence: 99%
See 1 more Smart Citation
“…49,50,[332][333][334][335][336][337][338][339][340] In a systematic review of observational studies between 1966 and 1997 that reported on outcomes with various anticoagulant regimens in pregnant women with mechanical prosthetic valves, the regimen associated with the lowest risk of valve thrombosis/systemic embolism was the use of vitamin K antagonists throughout pregnancy (3.9%). 49 The use of UFH in the fi rst trimester and near term was associated with a higher risk of valve thrombosis (9.2%).…”
Section: Anticoagulant Management Of Mechanical Prosthetic Valves In mentioning
confidence: 99%
“…332 Another systematic review of LMWH use in pregnant women with mechanical prosthetic heart valves that used slightly different eligibility criteria found that valve thrombosis occurred in seven of 81 pregnancies (8.6%; 95% CI, 2.5%-14.8%), and the overall thromboembolic rate was 10 of 81 pregnancies (12.4%; 95% CI, 5.2%-19.5%). 333 However, nine of the 10 patients with thromboembolic complications received a fi xed dose of LMWH, and in two of these, a fi xed low dose was used. Among 51 pregnancies in which anti-Xa LMWH levels were monitored and doses adjusted according to the result, only one patient was reported to have experienced a thromboembolic complication.…”
Section: E725smentioning
confidence: 99%
“…4 In another review, Oran et al found an overall incidence of valve thrombosis of 8.64% (8/81) and the overall TE rate 12.35% (10/81). 5 However, 9 of these 10 patients received a fixed dose of LMWH, and in 2 of these a low fixed dose was used. Among 51 pregnancies where antiXa levels were monitored, only one patient was reported to have had TE.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[17][18][19][20] Tüm gebelik boyunca DMAH kullanıldığında herhangi bir tromboembolik komplikasyon oranı %12.3 kapak trombozu oranı ise %8.6 olarak bildirilirken, [17] bir başka çalışmada maternal tromboembolik olay oranı %4 [18] olarak bildirilmiştir. Saeed ve ark.…”
Section: Discussionunclassified